Fabrication and characterization of hazelnut shell powders-loaded poly (lactic acid) (PLA) composite fibers - KARTAL, İLYAS (My University, 2023)
In this research, fibers were obtained by adding hazelnut shell powders which are a natural filler material (HSP) at different concentrations into Poly (lactic acid) (PLA) by using the electrospinning method, which is the most common method to obtain fibers. Scanning electron microscope (SEM), Fourier transform infrared spectroscopy (FTIR), tensile strength measurement, and physical analysis such as density, surface tension, viscosity, electrical conductivity test was performed after the fiber production process. The results obtained from this study, fibers showed beadles and smooth surfaces. The diameter distribution of these fibers was observed at 2092 µm without hazelnut shell powder. HSP was added to the composites (ϕ=2379,64±635,268 µm for b; ϕ=25581000,339±,806 µm for c; ϕ=2619,24±967,364µm) and diameters were increased. This result had shown, that by increasing the HSP proportion in the PLA/HSP solution, the average diameters of the fibers were increased. The tensile strength of the fibers decreased between the s1-s4 specimens. It has been shown that the tensile strength decreases as the diameter increases. The resulting structures of the fibers possessed antiseptic properties, which are attractive for many biomedical applications.
Keywords: Kimya; Temel Bilimler; Chemistry; Natural Sciences; Temel Bilimler (SCI); Natural Sciences (SCI); CHEMISTRY; Genel Kimya; Fizik Bilimleri; General Chemistry; Physical Sciences; Electrospinning; Fiber; Hazelnut shell powder; Poly (lactic acid); Electrospinning; Poly (lactic acid); Hazelnut shell powder; Fiber